Frontiers of Monetary Policymaking : Adding the Exchange Rate as a Tool to Combat Deflationary Risks in the Czech Republic - Alichi, Ali (IMF Working Papers; Working Paper ;, 2015)
The paper first describes how the Czech National Bank (CNB) moved gradually from a fixed exchange rate regime to the frontiers of Inflation-Forecast Targeting. It then focuses on the CNB's recent experience in adding the exchange rate as a complementary monetary policy tool to stimulate the economy and combat the risks of deflation when the policy interest rate is at the zero lower bound. It assesses the theoretical basis of such a policy, the communications approach used by the CNB when announcing the new framework, and the effects thus far on inflation and output.